2014
DOI: 10.1073/pnas.1409653111
|View full text |Cite
|
Sign up to set email alerts
|

Hominoid-specific enzyme GLUD2 promotes growth of IDH1 R132H glioma

Abstract: Somatic mutation of isocitrate dehydrogenase 1 (IDH1) is now recognized as the most common initiating event for secondary glioblastoma, a brain tumor type arising with high frequency in the frontal lobe. A puzzling feature of IDH1 mutation is the selective manifestation of glioma as the only neoplasm frequently associated with early postzygotic occurrence of this genomic alteration. We report here that IDH1 R132H exhibits a growth-inhibitory effect that is abrogated in the presence of glutamate dehydrogenase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
78
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 32 publications
10
78
1
1
Order By: Relevance
“…Instead, metabolic differences between GLUD2 + and control mice center on the metabolic pathways surrounding the TCA cycle. In agreement with this, it has been reported that overexpression of human GLUD2, but not GLUD1, in mutant murine glioma progenitor cells results in shunting of carbon into lipid biosynthesis via the TCA cycle (12). Our data further show that metabolic differences between GLUD2…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Instead, metabolic differences between GLUD2 + and control mice center on the metabolic pathways surrounding the TCA cycle. In agreement with this, it has been reported that overexpression of human GLUD2, but not GLUD1, in mutant murine glioma progenitor cells results in shunting of carbon into lipid biosynthesis via the TCA cycle (12). Our data further show that metabolic differences between GLUD2…”
Section: Discussionsupporting
confidence: 93%
“…However, the connection between the emergence of the GLUD2 gene in the ancestors of apes and humans and changes in brain function remains elusive. To date, the only direct insights into GLUD2 function come from a rare GLUD2 mutation linked to the onset of Parkinson's disease (11) and from glioma cells carrying a mutated isocitrate dehydrogenase 1 gene (IDH1) where GLUD2 expression reverses the effects of the IDH1 mutation by reactivation of the metabolic flux from glucose and glutamine to lipids by way of the TCA cycle (12).…”
mentioning
confidence: 99%
“…In all, our results suggest that altered oxidative stress response is the most likely downstream element of causing mitochondrial ROS (54). In addition, other Achilles' heels in IDH MT metabolism could be exploited, such as mitochondrial dysfunction (50), increased dependence on glutaminolysis (2,(55)(56)(57)(58)(59) and oxidative phosphorylation (42,43). These vulnerabilities can be pharmacologically targeted via BCL-2 inhibitors, chloroquine, and metformin, respectively.…”
Section: Idhmentioning
confidence: 86%
“…For example, a glioblastoma cell line and transformed astrocytes both exhibited increased sensitivity to pharmacological or siRNA-mediated inhibition of glutaminase (Seltzer et al, 2010). In addition, Chen et al recently observed that gliomas harboring IDH1 mutations overexpressed glutamate dehydrogenase 1 and 2 ( GLUD1 and GLUD2 ), and orthotopic growth of mutant glioma lines were sensitive to GLUD1 or GLUD2 knockdown (Chen et al, 2014). We observed a similar increase in the dependence of IDH1 mutant cells on glutaminolysis in our analysis of a panel of HCT116 cells, providing evidence that these changes arise due to a direct impact on metabolism rather than indirectly through cell lineage-specific mechanisms (Grassian et al, 2014).…”
Section: Glutaminolysis Reductive Carboxylation and Tca Metabolismmentioning
confidence: 99%